From coherence towards commitment: Changes and challenges in Zambia's nutrition policy environment - Harris, Jody; Drimie, Scott; Roopnaraine, Terence; Covic, Namukolo (Elsevier, 2017)
An enabling environment for malnutrition reduction includes creating policy and political momentum, and converting momentum to implementation and impact. We used several qualitative data sources to investigate changes in policy and action over time in Zambia. There now exists coherent policy covering key nutrition issues from several sectors, and multisectoral coordination structures at national level and in pilot districts. However, converting momentum into action faces challenges of limited national political and funding commitment, with increased donor resources currently bridging the gap, and reach into communities is still limited. To sustain recent stunting reductions there are still political challenges to be addressed in Zambia, and citizens and civil society will need to hold government to account for recent commitments on nutrition.